The NRF2, Thioredoxin, and Glutathione System in Tumorigenesis and Anticancer Therapies - Morana Jaganjac; Lidija Milkovic; Suzana Borovic Sunjic; Neven Zarkovic (MDPI AG, 2020)
Cancer remains an elusive, highly complex disease and a global burden. Constant change by acquired mutations and metabolic reprogramming contribute to the high inter- and intratumor heterogeneity of malignant cells, their selective growth advantage, and their resistance to anticancer therapies. In the modern era of integrative biomedicine, realizing that a personalized approach could benefit therapy treatments and patients' prognosis, we should focus on cancer-driving advantageous modifications. Namely, reactive oxygen species (ROS), known to act as regulators of cellular metabolism and growth, exhibit both negative and positive activities, as do antioxidants with potential anticancer effects. Such complexity of oxidative homeostasis is sometimes overseen in the case of studies evaluating the effects of potential anticancer antioxidants. While cancer cells often produce more ROS due to their increased growth-favoring demands, numerous conventional anticancer therapies exploit this feature to ensure selective cancer cell death triggered by excessive ROS levels, also causing serious side effects. The activation of the cellular NRF2 (nuclear factor erythroid 2 like 2) pathway and induction of cytoprotective genes accompanies an increase in ROS levels. A plethora of specific targets, including those involved in thioredoxin (TRX) and glutathione (GSH) systems, are activated by NRF2. In this paper, we briefly review preclinical research findings on the interrelated roles of the NRF2 pathway and TRX and GSH systems, with focus given to clinical findings and their relevance in carcinogenesis and anticancer treatments.